Janice VanCleave's geometry for every kid : easy activities that make learning geometry fun. - VanCleave, Janice Pratt (New York : Wiley, 1994)
Uses simple problems and activities to teach kids ages eight to twelve about acute and obtuse angles, plane and space figures, and parallel and perpendicular lines.
Lineup -- What's the angle? -- Crossover -- Three-sided figures -- Four-sided figures -- Hidden figures -- Overlay -- Five-square figures -- Curvey figures -- Never-ending line -- Around and around -- Too odd -- Reverse copy -- Plane art-- What's next? -- Coverup -- Same size -- Pie? -- Dotted --Spacey -- Faces -- On the surface -- Toothpick magic -- Over and up -- Three-dimensional drawings.
Includes index.
Booklist.
Elem. School Library Collection.
Wilson's Children.
7.8.
7.8
Keywords: Geometry -- Juvenile literature; Geometry; Mathematical recreations; Geometry; Mathematical recreations